TINDAK ILOKUSI DALAM FILM MELODYLAN KARYA FAJAR NUGROS - Panamba, Merlinda L; Pandean, Mariam L.M.; Pua, Christo R. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2021)
ABSRACT     This research is titled Action Speech Ilokusi in Melodylan Film. In this study discussed a problem that is what are the Functions and Forms of Categories in Melodylan Film. This research aims to identify, classify, and explain the Ilokusi Act based on functions and categories in Melodylan Film that uses Leech and Searle theory with data supply method using simak techniques and note techniques. In the data analysis using PUP method with power techniques such as speech organ refren, other langue, writing, and speech partners.The results of the analysis of this study can be concluded that in film there is a follow-up based on functions consisting of competitive, fun, cooperation, and contradictory while in the form of the category of ilokusi found in this film consists of asertif, directive, commissionive, and expressive.Keywords: Illocutionary Action, Function, Category